Effect of testosterone on blood-clotting markers in transsexual men - Estella Thaisa Sontag dos Reis; Carla Maria Franco Dias; Carolina Sales Vieira; Mariane Nunes Nadai; Sérgio Henrique Pires Okano; Silvio Antônio Franceschini; Lúcia Alves da Silva Lara (Hematology, Transfusion and Cell Therapy)
Background: The use of testosterone in gender-affirming hormone therapy for trans men is associated with several adverse effects. However, research on the risk of venous thromboembolism in this treatment remains limited and inconclusive. This study aimed to assess the impact of intramuscular testosterone on specific direct and indirect blood-clotting markers in trans men. Method: Treatment of trans men without previous use of testosterone was followed up in a prospective observational study in a trans people healthcare service. Gender-affirming hormone therapy was initiated with intramuscular testosterone cypionate (Depo-Testosterone). The blood-clotting markers prothrombin time, activated partial thromboplastin time, d-dimer, antithrombin, and factors VIII and VII were evaluated before and 12 weeks after starting the medication. Results: Nineteen trans men with a mean age of 23.7 ± 3.7 years were enrolled. After 12 weeks of hormone therapy, significant increases in weight (p-value = 0.002) and body mass index (p-value = 0.007) were observed in patients. Furthermore, there were significant increases of 830 % in serum testosterone (p-value = 0.000), 7 % in hemoglobin (p-value = 0.000) and 10 % in hematocrit (p-value = 0.001). Conversely, a 10 % decrease in high density lipoprotein cholesterol levels (p-value = 0.000), and 15 % decrease in Factor VII (p-value = 0.000) were detected. Conclusion: Intramuscular testosterone in trans men was associated with increases in hematocrit, hemoglobin, and the body mass index, and decreases in high density lipoprotein cholesterol and Factor VII. Nevertheless, these variables remained within normal reference values. Long-term follow-up studies evaluating gender-affirming hormone therapy with testosterone are needed to determine adequate risk management of venous and arterial thromboembolism in this population.